Construction of an Electrochemical Cell System Based on Carbon Composite Film Electrodes and its Application for Voltammetric Determination of Triclosan. Issue 9 (19th August 2014) - Libansky, Milan; Zima, Jiri; Barek, Jiri; Dejmkova, Hana
Abstract An array of carbon composite electrodes embedded in a 96 well microtitration plate was fabricated and applied for DPV determination of the environmental pollutant triclosan (5‐chloro‐2‐(2, 4‐dichlorophenoxy)‐phenol). For the preparation of composite electrodes, graphite and glassy carbon conductive microparticles were tested in combination with several types of polymers as nonconductive binders. For the measurements, combinations of graphitic carbon particles with polystyrene (C‐PS) and with polycarbonate (C‐PC) were selected. The achieved limit of detection was 0.49 µmol L−1 for C‐PS electrodes and 0.25 µmol L−1 for C‐PC electrodes in the selected optimum medium. The method was successfully applied for practical samples of river water and toothpaste.